Effects of Sleep Quality on Academic Performance of Children Aged 10 to 12: The Mediating Role of Updating Ability - Zhao, Xin (Best Evidence in Chinese Education, 2024)
Research has shown that sleep quality can positively predict academic performance of the student. Previous studies have focused on examining the correlation in secondary and tertiary education students, with little attention paid to that among primary school students. A recent cross-sectional study demonstrated that primary school students had higher risk of low sleep quality than other groups. Through a mediation model, this study investigated the relation between sleep quality and academic achievement in primary school students and the mediating effect of updating ability on this relationship.